Supply chain from production areas to Addis Ababa - Minten, Bart; Tamru, Seneshaw; Legesse, Ermias Engida; Kuma, Tadesse (International Food Policy Research Institute, 2018)
The importance of cities is rapidly growing. It is estimated that more than half of the world population was living in cities in 2010; this is up from 30 percent in the 1950s (UN Population Division 2010). Given this rapid urbanization, especially so in developing countries, and the increasing importance of the manufacturing and service sectors in these countries’ economies, more people are making a living outside agriculture. As part of this change, many more people do not grow their own food and rely on market purchases for their food needs. This results in rapidly increasing agricultural market flows, especially from rural to urban areas, with a high number of people on the production and consumption side depending on the functioning of these value chains. This dynamic has profound implications on people’s food security in developing countries.